Perspectives of HPV immunoprophylaxis in women over forty - Pertyński, Tomasz; Stachowiak, Grzegorz; Zając, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2008)
Oncogenic and non-oncogenic HPV infections are a problem not only for women aged 20-30, but also for older ones, over forty. So, effective prophylactic actions in premenopausal women should include not only secondary prophylaxis, but also all possible elements of primary prophylaxis. Although the most important part of this prophylaxis – a HPV vaccine – does not apply at the moment to women over forty, the preliminary results of FUTURE III – testifying to the high efficacy of the quadrivalent vaccine (HPV 6, 11, 16 and 18) in the group of women aged 35-45 – allow us to presume that the administration of effective immunoprophylaxis in premenopausal women will be possible in the near future.